Demanding Images : Democracy, Mediation, and the Image-Event in Indonesia - Strassler, Karen, 1969- (Book collections on Project MUSE., 2020)
"In DEMANDING IMAGES Karen Strassler uses the concept of image-event -- a period where images circulate in ways that contest and transform the public sphere -- to understand post-New Order Indonesia. Appropriated images, including images of Suharto and his historical opponents, recirculate, in street art, museums, newspapers, t-shirts, and stickers, forming a visual public sphere debating democracy and and new forms of corrupt governance in Indonesia's political present. The Reformasi movement in 1998 used images and the concept of transparency to represent the promise of democracy, and Strassler sees the recurrent images as a continual and shifting debate on that promised future. In a wider frame, Strassler's study of visual culture theorizes how ubiquitous political images are used by publics to confirm or deny the values of the political environment in which they circulate, while also shaping the values and seminal events that cause political publics to form in the first place. By building a theory of how political imaginaries circulate in the dense network of mass-produced and sub-cultural media, Strassler indicates the mutable and contingent nature of publics and political desire"--